Revitalising race equality policy? Assessing the impact of the Race Equality Charter mark for British universities. Issue 1 (2nd January 2022) - Campion, Karis; Clark, Ken
ABSTRACT: The Race Equality Charter (REC) was introduced in 2014 as a national policy initiative that aims to support UK universities in developing cultural and systemic changes to promote race equality for Black and minority ethnic (BME) staff and students. Drawing on quantitative data, we locate the REC within a complex picture of undergraduate student diversity and significant attainment gaps between white students and Black and ethnic minority groups. Using qualitative interviews and observations to further explore the questions our quantitative analysis raises, we show that the REC is not perceived as a significant vehicle for progressing race equality work in award-holding institutions. Rather, it is mostly applied as an enhancement tool to help shape and sustain existing race equality initiatives that produce incremental change. This, we argue, suggests the REC's intention to inspire race equality approaches that favour institutional strategic planning at the highest level, is yet to be realised.